2014
DOI: 10.1097/opx.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Between-Subject Variability in Asymmetry Analysis of Macular Thickness

Abstract: Purpose To investigate the use of Asymmetry Analysis to reduce between-subject variability of macular thickness measurements using SD-OCT. Methods 63 volunteers free of eye disease were recruited: 33 young subjects (ages 21 to 35 years), and 30 older subjects (ages 45 to 85 years). Macular images were gathered with the Spectralis OCT. An overlay 24°× 24° grid was divided into five zones per hemifield, and Asymmetry Analysis was computed as the difference between superior and inferior zone thicknesses. We hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Um et al 19 proposed using five zones that cover most of the posterior pole grid and mimic the glaucoma hemifield test. In a previous study from our laboratory, 20 we demonstrated that there was high normal between-subject variability of the asymmetry analysis in the peripheral regions of the grid, and this variation could be reduced using the asymmetry analysis. However, our study was limited by using retinal thickness measurements without segmenting out the ganglion cell layer and retinal nerve fiber layer, the most affected layers in patients with glaucoma.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…Um et al 19 proposed using five zones that cover most of the posterior pole grid and mimic the glaucoma hemifield test. In a previous study from our laboratory, 20 we demonstrated that there was high normal between-subject variability of the asymmetry analysis in the peripheral regions of the grid, and this variation could be reduced using the asymmetry analysis. However, our study was limited by using retinal thickness measurements without segmenting out the ganglion cell layer and retinal nerve fiber layer, the most affected layers in patients with glaucoma.…”
mentioning
confidence: 69%
“…Three zones were developed within the posterior pole grid based on regions with low between-subject variability that we found in our previous study, 20 in which normative data were collected from a homogenous group of young healthy control participants (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for the purpose of detailed investigation of eyes with glaucoma, a more layered approach may have some benefits. For instance, Curcio and Allen 21 reported that the ganglion cell topography varies along the different retinal meridians; however, other work 22 noted that the ganglion cell topography only contributes in a small proportion to the total macular shape. In glaucoma, outer retinal changes such as photoreceptor swelling may also occur additionally 23 contributing to differences in whole retinal thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is variation of the RGC distribution in the retina among the human population and the macula is strong candidate for the site of least variability 50 . In addition,…”
Section: Introductionmentioning
confidence: 99%